Kleinzelliges Lungenkarzinom = Small cell lung cancer - Steins, Martin; Thomas, Michael (Der Onkologe, 2016)
BackgroundPrognostic improvements for patients with small cell lung cancer (SCLC) have been achieved within the last decade especially due to the use of radiotherapeutic treatment options.MethodsIn this article, an overview of the approved and current therapeutic approaches for the treatment of SCLC is presented.ResultsGiven the high potential for proliferation and metastatic spread in SCLC, systemic chemotherapy, preferably with a platinum/etoposide combination, is still the therapeutic basis. In limited stage disease this is performed, if possible, simultaneously with thoracic radiotherapy (TRT) followed by prophylactic cranial irradiation (PCI). In extended stage disease (ED), TRT also has therapeutic value for those patients who respond to chemotherapy. PCI generally shows a reduction in the risk for cerebral metastases, but is with regard to the improvement of overall survival in ED controversial.ConclusionChemotherapy together with radiooncology is of substantial relevance for survival of SCLC patients.